Loss of function mutations in HARS cause a spectrum of inherited peripheral neuropathies - Safka Brozkova, Dana; Deconinck, Tine; Griffin, Laurie Beth; Ferbert, Andreas; Haberlova, Jana; Mazanec, Radim; Lassuthova, Petra; Roth, Christian; Pilunthanakul, Thanita; Rautenstrauss, Bernd; Janecke, Andreas R; Zavadakova, Petra; et al. (Brain, 2015)
Inherited peripheral neuropathies are a genetically heterogeneous group of disorders characterized by distal muscle weakness and sensory loss. Mutations in genes encoding aminoacyl-tRNA synthetases have been implicated in peripheral neuropathies, suggesting that these tRNA charging enzymes are uniquely important for the peripheral nerve. Recently, a mutation in histidyl-tRNA synthetase (HARS) was identified in a single patient with a late-onset, sensory-predominant peripheral neuropathy; however, the genetic evidence was lacking, making the significance of the finding unclear. Here, we present clinical, genetic, and functional data that implicate HARS mutations in inherited peripheral neuropathies. The associated phenotypic spectrum is broad and encompasses axonal and demyelinating motor and sensory neuropathies, including four young patients presenting with pure motor axonal neuropathy. Genome-wide linkage studies in combination with whole-exome and conventional sequencing revealed four distinct and previously unreported heterozygous HARS mutations segregating with autosomal dominant peripheral neuropathy in four unrelated families (p.Thr132Ile, p.Pro134His, p.Asp175Glu and p.Asp364Tyr). All mutations cause a loss of function in yeast complementation assays, and p.Asp364Tyr is dominantly neurotoxic in a Caenorhabditis elegans model. This study demonstrates the role of HARS mutations in peripheral neuropathy and expands the genetic and clinical spectrum of aminoacyl-tRNA synthetase-related human disease.
Keywords: neurodegeneration; Genetic Linkage; Histidine-tRNA Ligase; mužské pohlaví; rodokmen; Pedigree; Charcotova-Marieova-Toothova nemoc; genetická vazba; mutace; molecular genetics; Charcot-Marie-Tooth Disease; nemoci periferního nervového systému; Hereditary Sensory and Autonomic Neuropathies; dědičné senzorické a autonomní neuropatie; ženské pohlaví; Mutation; Humans; histidin-tRNA-ligasa; RNA processing; hereditary motor and sensory neuropathies; Peripheral Nervous System Diseases; whole-exome sequencing; Female; lidé; Male